Gambaran Fungsi Kognitif pada Lanjut Usia di Desa Sendangan Kecamatan Remboken - Roring, Nadia V.; nadia.roring@gmail.com, Junita M.; Mahama, Corry N. (Universitas Sam Ratulangi, 2020)
Abstract: Increased elderly in Indonesia grows in number and affects the health problems such as impaired cognitive function. Examination carried out by using Indonesian version Montreal Cognitive Assessment (MoCA-INA), Trail Making Test (TMT), and the Clock Drawing Test (CDT) are used to determine the cognitive function. This study was aimed to obtain the profile of cognitive function among the elderly at nursing home and outside of nursing home at Sendangan, Remboken. This was a descriptive study with a cross sectional design. The results showed that there were 59 people that met inculsion criteria. The Ina-MoCA examination showed that 94.9% of the elderly had a decline in cognitive function. Moreover, the TMT-A and TMT-B found that 100% of the elderly had impaired cognitive function. Meanwhile, the CDT found that 49.2% of the elderly had impaired cognitive function. In conclusion, the Ina-MoCA, TMT-A, TMT-B, and CDT indicated that the majority of the elderly at Sendangan, Remboken had impaired cognitive function.Keywords: elderly, cognitive function, Ina MoCA, TMT-A, TMT-B, CDTÂ Abstrak: Peningkatan lanjut usia di Indonesia semakin bertambah yang berdampak pada masalah kesehatan, salah satunya ialah gangguan fungsi kognitif. Pemeriksaan Montreal Cognitive Assesment versi Indonesia (INA-MoCA), Trail Making Test (TMT), dan Clock Drawing Test (CDT) dapat digunakan untuk medeteksi gangguan fungsi kognitif, Penelitian ini bertujuan untuk mengetahui gambaran fungsi kognitif pada lanjut usia di Panti Werdha dan luar Panti Werdha di Desa Sendangan Kecamatan Remboken. Jenis penelitian ialah deskriptif dengan desain potong lintang. Hasil penelitian mendapatkan 59 orang yang memenuhi kriteria penelitian. Pemeriksaan Ina-MoCA menunjukkan 94,9% lanjut usia mengalami penurunan fungsi kognitif. Pada pemeriksaan TMT-A dan TMT-B didapatkan 100% lanjut usia terganggu. Pemeriksaan CDT mendapatkan 49,2% lanjut usia terganggu. Simpulan penelitian ini ialah hasil pemeriksaan Ina-MoCA, TMT-A, TMT-B, dan CDT menunjukkan bahwa sebagian besar lansia di Desa Sendangan Kecamatan Remboken memiliki fungsi kognitif yang terganggu.Kata kunci: lanjut usia, fungsi kognitif, Ina MoCA, TMT-A, TMT-B, CDT